Vite, Rideau. (Bruxelles : Séraphine Graphics, 2021)
Gromilovic, Davor ; Svirplyte, Indre ; Vandewalle, Lotte ; Masse, Quentin ; Pion, Adele ; Diaz, Noélia ; Marien, Dennis ; Dandoy, Laurent ; Saitas, Iason ; Khachatryan, Shamiram ; Schiavone, Alice ; Caramin, Anneke ; Van den Wijngaert, Tom ; Sauvand, Coline ; Sarlat, Justine ; Bijleveld, Vincent ; Van De Geer, Hans ; Hottois, Noémie ; Shaw, Greg ; Drachman, Dido ; Dierickx, Kato ; Arendt, Maria
Nr. 11 in the Vite fanzine series was inspired originally by an exposition of large works on fabric. It features 80pg, full color digital print on acid-free Lessebo paper. You'll find works by established artists such as Lotte Vandewalle, Laurent Dandoy and Davor Gromilovic next to fresh works by younger authors, such as Dido Drachman, Indre Svirplyte and Vincent Bijleveld. Limited series, 100 copies, printed in Brussels. (provided by publisher)
boek